Snake bite. - Warrell, D (2010)
Snake bite is a common and frequently devastating environmental and occupational disease, especially in rural areas of tropical developing countries. Its public health importance has been largely ignored by medical science. Snake venoms are rich in protein and peptide toxins that have specificity for a wide range of tissue receptors, making them clinically challenging and scientifically fascinating, especially for drug design. Although the full burden of human suffering attributable to snake bite remains obscure, hundreds of thousands of people are known to be envenomed and tens of thousands are killed or maimed by snakes every year. Preventive efforts should be aimed towards education of affected communities to use proper footwear and to reduce the risk of contact with snakes to a minimum through understanding of snakes' behaviour. To treat envenoming, the production and clinical use of antivenom must be improved. Increased collaboration between clinicians, epidemiologists, and laboratory toxinologists should enhance the understanding and treatment of envenoming.